A Thromboxane A2 Receptor-Driven COX-2–Dependent Feedback Loop That Affects Endothelial Homeostasis and Angiogenesis. Issue 4 (3rd March 2022) - Eckenstaler, Robert; Ripperger, Anne; Hauke, Michael; Petermann, Markus; Hemkemeyer, Sandra A.; Schwedhelm, Edzard; Ergün, Süleyman; Frye, Maike; Werz, Oliver; Koeberle, Andreas; Braun, Heike; Benndorf, Ralf A.
Abstract : Background: TP (thromboxane A2 receptor) plays an eminent role in the pathophysiology of endothelial dysfunction and cardiovascular disease. Moreover, its expression is reported to increase in the intimal layer of blood vessels of cardiovascular high-risk individuals. Yet it is unknown, whether TP upregulation per se has the potential to affect the homeostasis of the vascular endothelium. Methods: We combined global transcriptome analysis, lipid mediator profiling, functional cell analyses, and in vivo angiogenesis assays to study the effects of endothelial TP overexpression or knockdown/knockout on the angiogenic capacity of endothelial cells in vitro and in vivo. Results: Here we report that endothelial TP expression induces COX-2 (cyclooxygenase-2) in a Gi/o - and Gq/11 -dependent manner, thereby promoting its own activation via the auto/paracrine release of TP agonists, such as PGH2 (prostaglandin H2 ) or prostaglandin F2 but not TxA2 (thromboxane A2 ). TP overexpression induces endothelial cell tension and aberrant cell morphology, affects focal adhesion dynamics, and inhibits the angiogenic capacity of human endothelial cells in vitro and in vivo, whereas TP knockdown or endothelial-specific TP knockout exerts opposing effects. Consequently, this TP-dependent feedback loop is disrupted by pharmacological TP or COX-2 inhibition and by genetic reconstitution of PGH2 -metabolizing prostacyclin synthase even in the absence of functional prostacyclin receptor expression. Conclusions: Our work uncovers a TP-driven COX-2–dependent feedback loop and important effector mechanisms that directly link TP upregulation to angiostatic TP signaling in endothelial cells. By these previously unrecognized mechanisms, pathological endothelial upregulation of the TP could directly foster endothelial dysfunction, microvascular rarefaction, and systemic hypertension even in the absence of exogenous sources of TP agonists.